Efeitos anestésicos da associação de Tramadol ou Clonidina à Lidocaína na anestesia peridual em cadelas - Rigueira, Fábio Di Lauro (2006)
The association of opioids or 2-agonists to local anesthetic agents may improve the quality of the epidural anaesthesia without increasing the occurrence of side effects. The aim of the present work was to evaluate the anesthetic effects obtained from the association between epidural tramadol or clonidine and lidocaine in female dogs. To do so, eleven adult female dogs with no defined breed weighting from 5 to 16 kg were used in a double blind study. The animals were submitted to three treatments with a two-week interval between them. In all treatments, the animals were pre-medicated with midazolam and anesthetized with propofol and subsequent epidural anesthesia performed between L7-S1. In treatment I (GL), lidocaine was used alone; in treatment II (GT), lidocaine was associated to tramadol (1 mg/Kg) and in treatment III (GC), lidocaine was associated to clonidine (150 mcg). The following parameters were evaluated: heart rate (HR), respiratory frequency (RF), mean arterial blood pressure (MBP), oxygen peripheral saturation (SpO2), temperature (T), sedation level, motor and sensitive latency, motor and sensitive block time and block cranial extension. Eventual side effects were also recorded. No differences between GL and GT were observed for none of the variables analyzed except for a higher block cranial extension in GT. Significant reduction on the HR, RF and T was verified in GC in relation to GL and GT and an increase on the motor and sensitive block times and a higher cranial extension of the anesthetic block were also observed. The main adverse effect observed in GT was itching and in GC was bradycardia and hypothermia. One may conclude that tramadol did not change the variables analyzed or the quality of the anesthetic block; clonidine improved the quality of the anesthetic block and extended its duration; however, with more side effects.